Analysis and assessment of heavy metals in urban surface on multivariate analysis - Moura, Márcio Cleto Soares de; Moita, Graziella Ciaramella; Moita Neto, José Machado (Federal University of Piauí, 2010)
The concentration of Cu, Pb, Zn, Cr, Ni and Mn in the surface soil samples from Teresina city were measured by flame atomic absorption spectrometry (FAAS). A total of 28 composite soil samples were collected at depths 0-10 cm, including residential districts, urban parks, green areas, vegetable-garden, heavy- and low-traffic density areas. Principal component analysis (PCA) and hierarchical cluster analysis (HCA) were used to analyze the data and identify possible sources of these heavy metals. The results of the multivariate analysis showed that Cu, Pb, Zn and Cr were associated mainly to anthropogenic activities, such as, fertilizer and vehicle emission. While Ni and Mn were controlled by original materials and therefore interpreted as natural sources.